Neuropharmacology of performance monitoring. - Jocham, G; Ullsperger, M (2009)
Adaptive, goal-directed behavior requires that organisms evaluate their actions in terms of their outcomes. Neuroimaging studies show that unfavorable outcomes or situations with high level of conflict engage the posterior medial frontal cortex (pMFC). Recording of event-related potentials revealed that these situations are accompanied by a negative deflection, the so-called error-related negativity (ERN), which appears after an erroneous response or after negative feedback. Both activation of the pMFC and the ERN are thought to represent a signal that indicates the need for behavioral adjustment, and to recruit other brain regions that implement these adjustments. While many fMRI and EEG studies have shed light on the anatomical structures and the cognitive processes involved in performance monitoring, only very recently have researchers begun to investigate the underlying neurochemical mechanisms. Drawing on the putative involvement of dopamine (DA) neurons in coding a reward prediction error, an influential theory has ascribed a pivotal role to DA in performance monitoring. However, although important, DA is certainly not the only neuromodulator involved. Recent studies point to a role for serotonin, norepinephrine and GABA, but also for adenosine in performance monitoring. Here, we review the evidence for neurotransmitter effects on this function in humans. In this light, we critically discuss currently debated models of performance monitoring and potential alternatives.